(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
This study assessed the psychological wellbeing of student-athletes and non-athletes at the University of Ilorin, employing a descriptive research design. The population included all University’s students, with 149 participants selected through a multi-stage sampling process. Stratified sampling categorised students into athletes (77) and non-athletes (72) chosen via random sampling. Data were collected using the General Health Questionnaire (GHQ-12), validated with Pearson’s product-moment correlation reliability coefficient of .73. Descriptive statistics, including frequency counts and percentages, addressed research questions, while an independent samples t test at a .05 alpha level was used to test hypotheses. The findings revealed no significant difference in psychological wellbeing between student-athletes and non-athletes. Additionally, the perception of the impact of sport on psychological wellbeing did not differ between the groups. The study concluded that both student-athletes and non-athletes at the University of Ilorin exhibit similar psychological wellbeing, and their views on the influence of sport on wellbeing are consistent regardless of participation. These findings suggest that sport participation does not uniquely affect psychological wellbeing in this context, emphasising the importance of universal stress management practices for all students. To enhance psychological health, the study recommends that both groups engage in stress-reducing activities such as meditation, deep breathing, or yoga. Keywords: psychological wellbeing, student-athlete, non-athlete, health status, University of Ilorin